2018
DOI: 10.1038/s41598-018-23065-3
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy maintains stem cells and intestinal homeostasis in Drosophila

Abstract: Intestinal homeostasis is maintained by tightly controlled proliferation and differentiation of tissue-resident multipotent stem cells during aging and regeneration, which ensures organismal adaptation. Here we show that autophagy is required in Drosophila intestinal stem cells to sustain proliferation, and preserves the stem cell pool. Autophagy-deficient stem cells show elevated DNA damage and cell cycle arrest during aging, and are frequently eliminated via JNK-mediated apoptosis. Interestingly, loss of Chk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 54 publications
3
32
1
Order By: Relevance
“…indicates that ISC dysfunction can develop independently of the described bacterial dysbiosis and inflammatory response. Recent studies have described a loss of proteostatic capacity in older ISCs due to a loss of Nrf2 activity (102), a decline of mitochondrial function in stem and progenitor cells (49), increased endoplasmic reticulum stress (93), activation of retrotransposon expression and ensuing DNA damage (103), changes in autophagy (104) and heterochromatin (105), and increased polymerase III transcriptional activity (106). All of these mechanisms seem to contribute to dysplasia in the aging intestine, yet it remains unclear how these processes interact at the level of the stem cell and with the wider inflammatory condition developing in the epithelium (90)(91)(92)(93)(94)(95).…”
Section: Age-related Dysfunction In a Variety Of Intrinsic Signaling mentioning
confidence: 99%
See 1 more Smart Citation
“…indicates that ISC dysfunction can develop independently of the described bacterial dysbiosis and inflammatory response. Recent studies have described a loss of proteostatic capacity in older ISCs due to a loss of Nrf2 activity (102), a decline of mitochondrial function in stem and progenitor cells (49), increased endoplasmic reticulum stress (93), activation of retrotransposon expression and ensuing DNA damage (103), changes in autophagy (104) and heterochromatin (105), and increased polymerase III transcriptional activity (106). All of these mechanisms seem to contribute to dysplasia in the aging intestine, yet it remains unclear how these processes interact at the level of the stem cell and with the wider inflammatory condition developing in the epithelium (90)(91)(92)(93)(94)(95).…”
Section: Age-related Dysfunction In a Variety Of Intrinsic Signaling mentioning
confidence: 99%
“…All of these mechanisms seem to contribute to dysplasia in the aging intestine, yet it remains unclear how these processes interact at the level of the stem cell and with the wider inflammatory condition developing in the epithelium (90)(91)(92)(93)(94)(95). Strikingly, ISCs of old flies also display frequent somatic mutations, resulting in neoplasias (94), and the fly intestine may thus also serve as a model for the age-related increase in cancer formation in vertebrates (49,(90)(91)(92)(93)(94)(95)104). These stem cell-intrinsic mechanisms of age-related decline also serve as targets for interventions, as improved homeostasis, and in some cases even life span extension, was observed when perturbations were targeted toward ISCs in the studies described above (93,(103)(104)(105)(106).…”
Section: Age-related Dysfunction In a Variety Of Intrinsic Signaling mentioning
confidence: 99%
“…Notably, accumulation of polyubiquitinated proteins in neurons deficient of autophagy increases the size and number of aging cells . Inhibition of autophagy by targeting different steps in the formation of the autophagosome through various Atg genes in the primordial gut of Drosophila showed suppression of the autophagic degradation function . Consequently, in eukaryotes, the regulation of every step of autophagy is vital for the integrity of tissue homeostasis and is responsible for controlling the organism's aging process.…”
Section: Autophagy In Eukaryotes: From Plants To Mammalsmentioning
confidence: 99%
“…The intestinal mucosa is one of the most active places in the mammalian body [16]. Intestinal epithelial cells are continuously self-renewing because the stem cells located in the intestinal crypt possess a strong ability to proliferate and differentiate into absorption cells, goblet cells, endocrine cells and Paneth cells, all of which not only maintain normal physiological functions but also repair damaged intestinal epithelium [16][17][18][19]. Although several reviews have shown that stem cell self-renewal and differentiation depend on the activation of autophagy [20,21], whether the autophagy of intestinal stem cell involves in the intestinal barrier and mucosal homeostasis is unknown.…”
Section: Introductionmentioning
confidence: 99%